Regional Estimates of Residential Electricity Demand in Brazil - Carrasco-Gutierrez, Carlos Enrique; Ehrl, Philipp (International Journal of Energy Economics and Policy, 2023)
Understanding consumers' short- and long-run response to electricity prices is essential for efficient market regulations, supplier planning decisions, and evaluation of policies for the economic development of the country. This work estimates the determinants of residential electricity demand for Brazil and for each of its five geographic regions, North, Northeast, Midwest, Southeast and South in a cointegration setup. The demand model accounts for the electricity prices, personal income, production and price of appliances, and climatic conditions, all of which show pronounced regional disparities. The data confirm that price and income elasticities are inelastic, both in the short- and long-run. Regional disaggregation yields the insight that price elasticities are insignificant in the North, Southeast and South, both in the short- and long-run. For the country as a whole, the short-term price effect is insignificant as well. This novel result casts doubt on recently implemented and future price-based policy measures that are necessary to reduce electricity consumption in a system that is frequently close to its maximum capacity. Brazil’s dependency on increasingly scarce rainfall and the rising electricity demand due to income increases require effective responses, however.